2002
DOI: 10.2136/sssaj2002.2840
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Diet Phosphorus Effects on Phosphorus Losses in Runoff from Land‐Applied Manure

Abstract: Phosphorus losses from land-applied manure can contribute to that the average dairy diet in the USA is supplemented nonpoint source pollution of surface waters. Dietary P forms and levels influence P concentrations in animal manures and may affect P to contain 4.8 g P kg Ϫ1 , while only 3.8 g P kg Ϫ1 is needed losses from land-applied manure. The objective of this study was to for optimum milk production and reproductive effidetermine the effects of dairy diet P concentration on P losses in ciency. This is a 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 18 publications
4
37
0
Order By: Relevance
“…This could potentially increase P runoff when manure is applied to cropland. Ebeling et al (2002) reported that P concentration in dairy diets influenced the forms and amounts of P in manure. Greater P concentration in the diet resulted iii greater dissolved reactive P in manure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could potentially increase P runoff when manure is applied to cropland. Ebeling et al (2002) reported that P concentration in dairy diets influenced the forms and amounts of P in manure. Greater P concentration in the diet resulted iii greater dissolved reactive P in manure.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary P intake influences the amount of P excreted in livestock manure (Morse et al, 1992;Wu et al. 2000;Ebeling et al 2002) and affects the amount of land necessary for manure application and the potential for 2The supplement provided 8,800,000 IU of vitamin A: 880,000 IU of vitamin D; and 880 mg/kg of vitamin E per kg. 'Trace mineral premix contained 13% Ca, 12% Zn, 8% Mn, 10% Fe.…”
Section: Introductionmentioning
confidence: 99%
“…This soluble P is more liable to P loss in runoff in comparison to particulate P. One study in the USA suggested that the P loss of cows fed a standard high P diet was 10 times that of cows fed with a lowered level of P, which was still adequate for milk production and cow health (Dou et al. , 2002; Ebeling et al. , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intensified livestock production has generated an increased production of organic residues and environmental regulations have been adopted for the application of manures in agriculture (Pandey, et al, 2001), as they are a diffuse source of pollution, with P in particular being directly associated with eutrophication in bodies of water (Haygarth and Jarvis, 1997;Gale et al, 2000;Withers et al, 2001;Ebeling et al, 2002;Hodgkinson et al, 2002;Ajiboye et al, 2004;He et al, 2004).…”
Section: Phosphorus In Manuresmentioning
confidence: 99%